Evaluar la calidad química y sensorial de las especies vieja colorada (Cichlasoma festae) y vieja azul (Andinocara rivulatus), comercializados en los mercados de Quevedo y Mocache - Montalvan Suárez, Adrián Arturo (2019)
This research investigation was carried out in the Chemistry Laboratory, located in the Experimental Farm "La María" of the State Technical University of Quevedo, located at km 7 ½ of the Quevedo - El Empalme road, San Felipe Campus; Canton Mocache, Province of Los Ríos. In Ecuador, many varieties of native fish are sold, including old red and old blue, which are unknown physical and chemical properties, which makes it difficult for the population to know the nutritional benefits of these species and identify based on organoleptic attributes in what state is the fish and if it is suitable for human consumption. The scarce nutritional information that exists in Ecuador of the native species and especially of the old red and blue Amerita studies are done that help to know the nutritional benefits that these species possess, in the areas of the riversides of the province of Los Ríos they are consumed daily and are the livelihood of many families who are engaged in fishing and selling these fish species. In the present investigation a completely randomized design (DCA) was used with a factorial arrangement of 2x2: the first factor (V) corresponds to the two species (Old red and blue) the second factor (M) corresponds to the markets (Quevedo y Mocache), with 5 repetitions for each treatment (4 treatments) giving a total of 20 experimental units. Keywords: Market, fish, minerals, proximal determination.